Building Human Relationship Toward Enhancing Service Delivery Effectiveness Among Homestay Operators in Malaysia - Abdul Mutalib, Siti Salwa; Abdul Razzaq, Abdul Rasid; Hasan, & Azman (Journal of Technical Education and Training, 2019)
Homestay program is an alternative form of tourism product in Malaysia. As it is highly connecting with customers, it is important to have an effective customer service delivery to increase level of satisfaction due to a few grievance reported in the journal about bad service quality of homestay in Malaysia. It is important to remain long term relationship with customer to ensure the profitability of homestay operation. To attract and getting the new customers is not a cost effective strategy. This study have been carried out to find a good way on building a good relationship with customers which can enhance customer service delivery effectiveness of homestay in Malaysia. This study have applied a qualitative approach by exploration research design. The researchers were conducted the interviews with five experts in related area purposively. The data was gathered from the literature reviews and interview session. The theme and category have been carried out before thematic analysis. The result of the study found that there are three main factors that have to be focus, (i) building rapport, (ii) maintain relationship, and (iii) service recovery. A good relationship should not only apply to the customer but also for the entire stakeholders in order to make the homestay program successful.